Arts and Culture as a Medium of Islamic Propagation. - Mutmainnah, Nurun Nisa; Arifuddin, Arifuddin (Jurnal Mercusuar, 2021)
Art is something that contains beauty, pleasure and everything that is interesting and enjoyable. Art is basically created to bring pleasure and beauty. Pleasure is a desire and preference of human beings due to the natural instincts blessed by Allah SWT, while beauty is a quality that refers to a person’s feelings towards an object that contains aesthetic value. Throughout human history, no one has ever been found to distance themselves from various forms of art. On the other hand, Da’wah is a call to duty that is not determined by social structure, position or skin color differences, but for all people who claim to be Muslims. The task of Da’wah is adjusted to the abilities and skills of each subject of Da’wah, which means that not everyone has to engage in Da’wah activities like a preacher, orator, or khateeb, but is based on their abilities and expertise. An artist can propagate the faith through their artworks, as artwork is a medium of providing understanding to the community about the beauty of Islam.